Prevalence pattern of dental caries in the primary dentition among school children - Saravanan S; Madivanan I; Subashini B; Felix J (Wolters Kluwer Medknow Publications, 2005)
The purpose of the study was to assess the pattern of prevalence of dental caries in the primary dentition among 5 year old children. The area of study was urban Pondicherry and the study population consisted of 1009 school children of both sexes (527 boys and 482 girls). A simple random sampling method was used to select the schools. Dental caries was assessed by the Dentition status and Treatment Need (WHO 1997). Statistical analysis was done using the Proportion test. The prevalence of caries was 44.4% among the study population, being higher in the boys (P < 0.05); In Mandibular arch in both the sexes (boys P < 0.05, girls P < 0.01); in posterior teeth (both sex wise & arch wise). Comparison of caries among anterior teeth (Boys vs Girls) [corrected] and posterior teeth (upper vs. lower) revealed higher caries prevalence in Maxillary anterior teeth (P < 0.001) and Mandibular posterior teeth (P < 0.001). In both the sexes and arches, primary second molars showed higher caries prevalence.